Metal conductive film for EC, method, assembly and application
By optimizing the structural design of the metal conductive film for EC (extension coil), and combining a double silver functional layer and a high refractive index capping layer, the problem of slow color change speed in EC technology has been solved, achieving low impedance, high light transmittance and high durability, making it suitable for scenarios such as automotive sunroofs and AR glasses.
Patent Information
- Application Number
- CN202511820121.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-04
- Publication Date
- 2026-01-27
AI Technical Summary
Existing EC technology is insufficient in terms of color-changing speed, making it difficult to meet the needs of scenarios with high response speed requirements, such as automotive sunroofs and AR glasses. It also suffers from high cost and limited color options.
By designing a double silver functional layer, interlayer optical matching, and a special capping layer, the structure of the metal conductive film for EC is optimized to achieve low impedance, high light transmittance, and high durability. Specifically, this includes a combination of a flexible substrate, a hardening layer, a silver functional layer, and a capping layer, and the use of doped metals and high refractive index materials to improve performance.
It has achieved an EC color-changing speed of ≤20s, maintained a high light transmittance of ≥83%, and improved the product's durability and reliability to meet the needs of different dimming scenarios.
Smart Images

Figure CN121411044A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of optics, and particularly relates to a metal conductive film for EC, a method, an assembly and application. BACKGROUND
[0002] The existing technical routes of light-adjustable color-changing mainly include PDLC (polymer dispersed liquid crystal), SPD (suspended particles), EC (electrochromic) and DLC, and each of the technical routes has advantages and disadvantages: (1) the PDLC technology has the lowest cost and the fastest color-changing speed (up to 150 ms), and has bronze, green and gray colors, but has poor ring test performance, and currently has a technical bottleneck; (2) the DLC technology has a color-changing speed of less than 1 s, but has high cost, and the color is limited to gray and black; (3) the SPD technology has a color-changing speed of 1-3 s, but has high cost, and the color is limited to blue; (4) the EC technology has very stable ring test performance, and has blue, black and gray colors, but has a color-changing speed of more than 1 min, and is difficult to meet the requirements of scenes such as automobile canopies and AR glasses which have high requirements on response speed.
[0003] Therefore, in view of the above technical problems, it is necessary to provide a metal conductive film for EC, a method, an assembly and application. SUMMARY
[0004] The application aims to provide a metal conductive film for EC, a method, an assembly and application, which realizes the synergistic performance of "low impedance (≤3 Ω / □) + high light transmittance (≥83%) + high durability (resistant to salt mist for 240 h and resistant to charging and discharging for 1000 h)" through the design of a double-silver functional layer, interlayer optical matching and special capping layer optimization, and meets the requirements of different EC light-adjustable scenes.
[0005] In order to achieve the above-mentioned purpose, the technical scheme provided by a specific embodiment of the application is as follows:
[0006] The metal conductive film for EC comprises, in sequence, a first hardening layer, a flexible substrate, a second hardening layer, a bottom capping layer, a first silver functional layer, an intermediate medium layer, a second silver functional layer, a first top capping layer and an external capping layer.
[0007] The total thickness of the first silver functional layer and the second silver functional layer is 14-18 nm, and d2-d1≤4 nm, wherein d1 is the thickness of the first silver functional layer, and d2 is the thickness of the second silver functional layer. In the scheme, the surface impedance of the conductive film can be ≤3 Ω / □, and the visible light band (380-780 nm) light transmittance can be ≥83%.
[0008] In one or more embodiments of the present application, the first silver functional layer and / or the second silver functional layer is a silver layer or a silver functional layer, wherein the silver functional layer is a silver layer doped with a doping metal at a doping atomic ratio of 0.5%-5%, and the doping metal is one or more of Ni, Cu, Co, Sn, Pd, and Cr. Preferably, the silver functional layer is a silver layer doped with a doping metal at a doping atomic ratio of 0.5%-2%. Preferably, the silver functional layer is prepared by vacuum plating, and the base vacuum is <1x10 -4 Pa, and the argon gas flow rate is 50-300sccm. After plating, the vacuum degree is 0.05-0.4Pa.
[0009] In one or more embodiments of the present application, the outer capping layer is a high-refractive material with a refractive index of 2.0-2.40, selected from one of Nb2O5, Si3N4, TiO2, and ZrO2, and the thickness is 5-30nm.
[0010] In one or more embodiments of the present application, the material of the bottom capping layer and / or the intermediate medium layer and / or the first top capping layer is mainly an oxide of In, Sn, Zn, and Cd or a composite multi-element oxide thereof, and the most preferred material is a film layer of zinc oxide, tin oxide, and stannous oxide. Preferably, the material of the bottom capping layer and / or the intermediate medium layer and / or the first top capping layer is zinc oxide or tin oxide or an Al-doped body (AZO, tin oxide / Al, etc.). Further preferably, the mass ratio of zinc oxide to aluminum oxide in the material of the bottom capping layer and / or the intermediate medium layer and / or the first top capping layer is 95:5%-99:1%. Preferably, the refractive index of the bottom capping layer, the intermediate medium layer, and the first top capping layer is 1.9-2.2, and the thicknesses are 15-40nm for the bottom capping layer, 20-95nm for the intermediate medium layer, and 5-30nm for the first top capping layer, respectively.
[0011] In one or more embodiments of the present application, the thickness of the flexible substrate is 0.05-3mm, and the raw material is selected from one or more of PET, PI, SRF, TAC, COP, PMMA, PE, PC, PP, PA, and TPU. Preferably, the raw material is PET or PI, and most preferably, the raw material is PET. The thickness of the flexible substrate is 0.05-3mm, preferably 0.1-1mm, and most preferably 0.1-0.3mm.
[0012] In one or more embodiments of the present invention, the refractive index of the first hardening layer and / or the second hardening layer is 1.46-1.56, the thickness is 0.1-5 μm, and the layer includes low-refractive-index particles, which are silicon oxide, aluminum oxide, or MgF2. Preferably, the low-refractive-index particles are silicon oxide. Preferably, the particle size of the low-refractive-index particles is 20 nm-3 μm. Preferably, the volume percentage of the low-refractive-index particles in the first hardening layer and / or the second hardening layer is 5-20%. Preferably, the first hardening layer and the second hardening layer have the same composition, both formed by coating a slurry composed of acrylate monomers, crosslinking agents, polymerization inhibitors, plasticizers, and low-refractive-index particles. Preferably, it can be prepared by a micro-grooved roller coating device or a slot coating device.
[0013] In one or more embodiments of the present invention, a second top capping layer is further formed between the first top capping layer and the outer capping layer, which is an Au layer with a thickness of 2-3.5 nm. Preferably, the extinction coefficient k value (550 nm) of the Au layer is 2.3, and it is prepared by vacuum evaporation or magnetron sputtering.
[0014] In one or more embodiments of the present invention, a method for preparing a metal conductive film for EC includes the following steps:
[0015] (1) Substrate pretreatment: Clean and dry the flexible substrate to remove surface oil and impurities;
[0016] (2) Hardening layer preparation: A first hardening layer and a second hardening layer are formed on both sides of the substrate by coating;
[0017] (3) Vacuum coating: A bottom capping layer, a first silver functional layer, an intermediate dielectric layer, a second silver functional layer, and a first top capping layer are sequentially prepared on the second hardened layer by magnetron sputtering. The first top capping layer may also selectively form any of the following:
[0018] a. External capping layer; b. Second top capping layer, external capping layer.
[0019] Preferably, the preparation method is characterized by comprising the following steps:
[0020] (1) Substrate pretreatment: Clean and dry the flexible substrate to remove surface oil and impurities;
[0021] (2) Hardening layer preparation: Hardening layer coating is applied to both sides of the substrate by micro-grooving roller or slit coating, and after curing, the first hardening layer and the second hardening layer are formed;
[0022] (3) Vacuum coating: The bottom capping layer, the first silver functional layer, the intermediate dielectric layer, the second silver functional layer, and the first top capping layer are sequentially prepared on the second hardened layer by magnetron sputtering;
[0023] (4) Structure forming: A high refractive index material is sputtered onto the first top capping layer to form an outer capping layer, thus obtaining the first structural conductive film; or
[0024] A second top capping layer (Au layer) is sputtered onto the first top capping layer, and then a high refractive index material is sputtered to form an outer capping layer, thus obtaining a second structure conductive film.
[0025] Preferably, the curing conditions for the hardening layer are: UV curing (UV intensity 800-1200 mJ / cm²) or heat curing (temperature 80-120℃, time 30-60 min).
[0026] Preferably, the magnetron sputtering power is 50-200W and the coating speed is 0.5-2m / min.
[0027] In one or more embodiments of the present invention, a dimming assembly includes a light-transmitting body and a metal conductive film for EC formed on the light-transmitting body.
[0028] In one or more embodiments of the present invention, the dimming component is used in a device having a window structure, the window structure including a frame and a dimming component disposed on the frame. The device to which this component is used may include a vehicle sunroof, a side window of a vehicle such as a vehicle, ship, or aircraft, architectural glass or AR glasses, a computer display, etc.
[0029] Compared with existing technologies, the present invention provides a metal conductive film, method, component, and application for EC (electrode color change). Through optimized structural design, it maintains superior performance, achieving low impedance, high transmittance, excellent salt spray resistance, and good charge-discharge stability. Furthermore, by optimizing the refractive index and thickness of the hardening layer, silver functional layer, and capping layer, it maintains high transmittance and reduces transmittance loss to less than 2%. This invention addresses the slow color-changing speed of EC technology by replacing the ITO conductive film with a metal conductive film (Ag), reducing impedance to below 3 ohms and significantly improving the color-changing speed (≤20s). Through film optical design, it maintains high transmittance, with a visible light transmittance ≥83%. Simultaneously, through process methods, using Ag alloys and adding optimized capping layers, it greatly improves the product's durability and reliability. Attached Figure Description
[0030] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0031] Figure 1 This is a schematic diagram of the structure of a metal conductive film for EC in one embodiment of the present invention, wherein a is a schematic diagram of the first structure conductive film and b is a schematic diagram of the second structure conductive film.
[0032] Figure 2 This is a schematic diagram of the charge-discharge experimental mechanism of a metal conductive film sample for EC in one embodiment of the present invention;
[0033] Figure 3 This is a schematic diagram of the DC pulse voltage setting for the charge-discharge experiment of the metal conductive film for EC in one embodiment of the present invention.
[0034] Explanation of key figure labels:
[0035] 1-First hardening layer, 2-Flexible substrate, 3-Second hardening layer, 4-Bottom capping layer, 5-First silver functional layer, 6-Intermediate dielectric layer, 7-Second silver functional layer, 8-First top capping layer, 9-Outer capping layer, 10-Second top capping layer. Detailed Implementation
[0036] To enable those skilled in the art to better understand the technical solutions in this disclosure, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments disclosed herein. Obviously, the described embodiments are only some embodiments of this disclosure, and not all embodiments. Based on the embodiments in this disclosure, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this disclosure.
[0037] like Figure 1 As shown in a and b, the metal conductive film for EC of the present invention can include two layered structures, both based on "flexible substrate + double-sided hardened layer", the difference being the design of the top capping layer, which adapts to different environmental resistance requirements:
[0038] First-structure conductive film (basic type): Suitable for applications with moderate environmental resistance requirements, such as architectural glass.
[0039] From bottom to top, the layers are as follows: First hardening layer (0.1-5μm) → Flexible substrate (0.05-3mm) → Second hardening layer (0.1-5μm) → Bottom capping layer (15-40nm) → First silver functional layer (d1) → Intermediate dielectric layer (20-45nm) → Second silver functional layer (d2) → First top capping layer (5-30nm) → Outer capping layer (5-30nm);
[0040] Where d1+d2=14-18nm, 0≤d2-d1≤4nm.
[0041] Second structure conductive film (high durability): suitable for applications requiring high environmental resistance, such as automotive sunroofs and AR glasses.
[0042] From bottom to top, the layers are as follows: First hardening layer (0.1-5μm) → Flexible substrate (0.05-3mm) → Second hardening layer (0.1-5μm) → Bottom capping layer (15-40nm) → First silver functional layer (d1) → Intermediate dielectric layer (50-95nm) → Second silver functional layer (d2) → First top capping layer (5-30nm) → Second top capping layer (Au layer, 2-3.5nm) → Outer capping layer (5-30nm);
[0043] Where d1+d2=14-18nm, 0nm≤d2-d1≤4nm. The thickness of the intermediate dielectric layer in the second structure is increased to 50-95nm, forming optical complementarity with the Au layer, ensuring that the transmittance loss is controlled within 2%.
[0044] Function and parameter optimization of each membrane layer
[0045] Flexible substrate: Provides a supporting framework, requiring a balance between strength and flexibility.
[0046] Material selection: PET or PI are preferred (for automotive applications where strength and stiffness are required), with PET being the best choice (low cost and good light transmittance).
[0047] Thickness control: 0.1-0.3mm (too thick affects flexibility, too thin makes it easy to deform).
[0048] First / Second hardening layer: Improves the substrate's abrasion resistance and scratch resistance, and assists in film winding.
[0049] Ingredients: Acrylic ester monomer (determines hardness) + crosslinking agent + polymerization inhibitor + silica particles (low refractive index, to avoid affecting light transmission);
[0050] Refractive index: 1.46-1.56 (matches the substrate to reduce interface reflection);
[0051] Preparation method: micro-grooved roller coating or slot coating (high precision, coating uniformity ≤ ±5%).
[0052] First / Second Silver Functional Layer: Core Conductive Layer, solving the problems of easy oxidation and conductivity decay of pure Ag.
[0053] Doping optimization: Adding metals such as Ni / Cu / Co (atomic ratio 0.5%-2%) to inhibit the reaction of Ag with O, S, and Cl, thereby improving oxidation resistance;
[0054] Thickness design: The total thickness of the double silver functional layer is 14-18nm (too thick a single silver layer will lead to a decrease in light transmittance, while too thin a layer will lead to an increase in impedance), and the difference between d2 and d1 is ≤4nm (to avoid optical interference imbalance).
[0055] Preparation process: vacuum magnetron sputtering (base vacuum < 1 × 10-4 Pa, Ar gas protection to avoid Ag oxidation).
[0056] Bottom cap layer, intermediate dielectric layer, first top cap layer: protection against Ag oxidation + optical matching
[0057] Materials: AZO (zinc oxide:aluminum oxide = 95%:5%-99%:1%) or tin oxide:Al (low absorption, high corrosion resistance, and Al doping increases carrier concentration and reduces interlayer impedance);
[0058] Refractive index: 1.9-2.2 (forms an optical transition with the silver functional layer, reducing reflection loss);
[0059] The second top capping layer / Au layer of the second structure conductive film: Utilize Au's excellent resistance to electrochemical corrosion to improve charge and discharge stability, but the thickness needs to be controlled at 2-3.5nm (too thick will cause a decrease in light transmittance of >2% due to Au's high extinction coefficient, while too thin will result in insufficient protection).
[0060] External capping layer: further optimizes light transmittance
[0061] Materials: Niobium pentoxide, silicon nitride, etc. (refractive index 2.0-2.40), which form optical complementarity with the substrate and reduce visible light reflection;
[0062] Thickness: 5-30nm (precise wavelength matching to achieve interference anti-reflection).
[0063] The optical matching mechanism of the metal conductive film for EC in this invention is as follows:
[0064] By synergistically controlling the refractive index (n) and thickness (t) of each film layer, "low reflection and high light transmittance" can be achieved.
[0065] Second hardening layer (n=1.46-1.56) → bottom capping layer (n=1.9-2.2): refractive index gradient transition to reduce specular reflection;
[0066] Double silver functional layer (total thickness 14-18nm): Utilizes the optical interference effect of the metal layer to cancel out some of the reflected light;
[0067] External capping layer (high refractive index n=2.0-2.40): forms a "low-medium-high" refractive index sequence with the underlying layer, covering the anti-reflection requirements of the visible light band;
[0068] Au layer of the second structure conductive film: By controlling the thickness (2-3.5nm), the transmittance loss is controlled to within 2% (from ≥86% of the first structure conductive film to ≥83% of the second structure conductive film).
[0069] Specifically, it can be further clarified as follows:
[0070] Substrate
[0071] The substrate can include film materials such as PET (polyethylene terephthalate), SRF (super-recursive polyester film PET), TAC (triacetyl cellulose), PI (polyimide), CPI (colorless polyimide), COP (cycloolefin polymer), PMMA (polymethyl methacrylate), PE (polyethylene), PC (polycarbonate), PP (polypropylene), PA (polyamide), and TPU (thermoplastic polyurethane elastomer), or it can be a composite film of two or more polymers, such as PET+TPU composite film, PC+PMMA composite film, etc. The product of this invention is mainly used in automotive sunroofs and side windows, which require a certain strength and rigidity from the substrate. Therefore, PET and PI materials are preferred as the substrate, with PET being the most preferred. The thickness is selected as 0.05-3mm, preferably 0.1-1mm, and most preferably 0.1-0.3mm.
[0072] First / Second Hardening Layer
[0073] Hard coating (HC) is a layer that enhances the hardness of the film material, providing wear resistance and scratch resistance. It is prepared on the substrate through a coating process. Precision coating methods such as gravure coating, comma roller coating, and slot-die coating can be used, with gravure coating and slot-die coating being preferred due to their high coating precision and uniformity.
[0074] The hardened layer of this invention is composed of acrylate monomers, crosslinking agents, polymerization inhibitors, plasticizers, etc., among which the acrylate monomers include methyl methacrylate, ethyl methacrylate, etc., which are the main factors determining the hardness and wear resistance of the HC layer. To accelerate the anti-adhesion effect of the HC layer, microparticles are added to the resin. Since the HC layer is a low refractive index material (refractive index 1.46-1.52), low refractive index material particles are preferred, such as silicon oxide particles, alumina, magnesium fluoride (MgF) particles, etc., with silicon oxide particles being the most preferred, as their refractive index is 1.46-1.56.
[0075] First / Second Silver Functional Layer
[0076] The silver functional layer was prepared by vacuum deposition, with a base vacuum of <1×10⁻⁶. -4 Pa, introduce 50-300 sccmAr, after the gas is introduced the vacuum degree is 0.05-0.4Pa, the power can be set to match the speed, and a thin silver functional layer of 5-10nm thickness is deposited.
[0077] Ag is chemically reactive and is an electrophilic metal. In the presence of oxygen, it readily reacts with oxygen to form silver oxide. Furthermore, silver readily reacts with sulfides and chlorides. Therefore, to ensure the stability of the product of this invention, appropriate anti-oxidation measures must be taken: 1) using alloyed Ag instead of pure Ag; and 2) adding protective layers to both sides of the silver functional layer.
[0078] Ag alloying is a common method in the coating industry. By doping with other metallic elements, certain properties can be enhanced, such as improving oxidation resistance, strength, and conductivity. This invention aims to improve the oxidation resistance of the silver functional layer. This requires adding one or more of the following metallic components to the Ag target: nickel (Ni), copper (Cu), cobalt (Co), tin (Sn), palladium (Pd), and chromium (Cr). The atomic ratio of these additions is generally 0.5%-5%, preferably 0.5%-2%.
[0079] Bottom cap layer / First cap layer
[0080] To ensure product usability, it is essential to suppress Ag oxidation. Besides using alloyed Ag instead of pure Ag, adding capping layers to both sides of the silver functional layer is also necessary. Simultaneously, to ensure high visible light transmittance, the capping layer needs to be a transparent dielectric film with low absorption and excellent corrosion resistance, such as oxides of In, Sn, Zn, and Cd, or their composite multi-element oxides. Zinc oxide, tin oxide, and stannous oxide films are preferred. Furthermore, to further enhance the oxidation resistance of the capping layer, composite multi-element oxides are used. The optimal solution is to dope zinc oxide and tin oxide films with Al. This not only significantly improves the oxidation resistance of zinc oxide and tin oxide films but also provides additional freely moving electrons, significantly increasing carrier concentration, greatly reducing resistivity, and thus significantly improving the conductivity of zinc oxide and tin oxide films.
[0081] The capping layer is prepared using vacuum deposition methods, including evaporation, magnetron sputtering, and ion plating. The zinc oxide or tin oxide-doped aluminum oxide in the capping layer can be obtained using hybrid target sputtering; for example, zinc oxide targets doped with Al are commonly used AZO targets.
[0082] The zinc oxide:aluminum oxide mass ratio is controlled between 95%:5% and 99%:1%. Additionally, Al is doped onto a Sn target, and a composite film of tin oxide mixed with aluminum oxide is prepared through a vacuum deposition oxygen-permeable reaction.
[0083] In addition, in order to maintain the low impedance (≤3Ω / □) and high transmittance (≥80%) of the metal conductive film for EC in this invention, it is necessary to control the refractive index and thickness of each layer of material. Low impedance and high transmittance can be achieved by matching the refractive index and thickness.
[0084] First structure conductive film:
[0085] Flexible substrates include PET, SRF, TAC, PI, etc., with PET and PI being preferred, and PET being the most preferred. The substrate thickness is selected from 0.05-3mm, preferably 0.1-1mm, and most preferably 0.1-0.3mm.
[0086] The primary function of the first / second hardening layer is to increase the hardness of the substrate, reduce mechanical scratches, and facilitate the winding of large rolls of film. Its main component is acrylic resin, with a refractive index range of 1.46-1.56 and a thickness range of 0.1um-5um.
[0087] The first / second silver functional layer mainly consists of adding one or more of the following metal components to the Ag target: nickel (Ni), copper (Cu), cobalt (Co), tin (Sn), palladium (Pd), and chromium (Cr). The proportion of added atoms is generally 0.5%-5%, preferably 0.5%-2%. The thickness of the first silver functional layer is d1, and the thickness of the second silver functional layer is d2. Then, 14nm ≤ d1 + d2 ≤ 18nm, and 0 ≤ d2 - d1 ≤ 4nm.
[0088] The bottom capping layer is primarily made of materials such as zinc oxide, tin oxide, and ITO, with a preferred option being a mixed dielectric layer of zinc oxide doped with Al (AZO) and tin suboxide doped with Al. The refractive index of the bottom capping layer ranges from 1.9 to 2.2, and the thickness ranges from 15 to 40 nm.
[0089] The intermediate dielectric layer is made of the same material as the bottom capping layer, primarily using zinc oxide, tin oxide, and ITO, or a mixed dielectric layer of zinc oxide doped with Al (AZO) or tin suboxide doped with Al. The refractive index of the bottom capping layer ranges from 1.9 to 2.2, and the thickness ranges from 20 to 45 nm.
[0090] The first top capping layer is made of the same material as the bottom capping layer, primarily using materials such as zinc oxide, tin oxide, and ITO, with a preferred option being a mixed dielectric layer of zinc oxide doped with Al (AZO) and tin suboxide doped with Al. The refractive index of the bottom capping layer ranges from 1.9 to 2.2, and its thickness ranges from 5 to 30 nm.
[0091] The outer capping layer is made of a high refractive index material, including but not limited to niobium pentoxide, silicon nitride, titanium oxide (TiO2), zirconium oxide (ZrO2), and other high refractive index oxides or nitrides. The refractive index of the outer capping layer is in the range of 2.0-2.40, and the thickness is in the range of 5-30nm.
[0092] Second structure conductive film:
[0093] Flexible substrates include PET, SRF, TAC, PI, etc., with PET and PI being preferred, and PET being the most preferred. The substrate thickness is selected from 0.05-3mm, preferably 0.1-1mm, and most preferably 0.1-0.3mm.
[0094] The primary function of the first / second hardening layer is to increase the hardness of the substrate, reduce mechanical scratches, and facilitate the winding of large rolls of film. Its main component is acrylic resin, with a refractive index range of 1.46-1.56 and a thickness range of 0.1um-5um.
[0095] The first / second silver functional layer mainly consists of adding one or more of the following metal components to the Ag target: nickel (Ni), copper (Cu), cobalt (Co), tin (Sn), palladium (Pd), and chromium (Cr). The proportion of added atoms is generally 0.5%-5%, preferably 0.5%-2%. The thickness of the bottom first silver functional layer is d1, and the thickness of the top second silver functional layer is d2. Therefore, 14nm ≤ d1 + d2 ≤ 18nm, and 0nm ≤ d2 - d1 ≤ 4nm.
[0096] The bottom capping layer is primarily made of materials such as zinc oxide, tin oxide, and ITO, with a preferred option being a mixed dielectric layer of zinc oxide doped with Al (AZO) and tin suboxide doped with Al. The refractive index of the bottom capping layer ranges from 1.9 to 2.2, and the thickness ranges from 15 to 40 nm.
[0097] The intermediate dielectric layer is made of the same material as the bottom capping layer, primarily using zinc oxide, tin oxide, and ITO, or a mixed dielectric layer of zinc oxide doped with Al (AZO) or tin suboxide doped with Al. The refractive index of the bottom capping layer ranges from 1.9 to 2.2, and the thickness ranges from 50 to 95 nm.
[0098] The first top capping layer is made of the same material as the bottom capping layer, primarily using materials such as zinc oxide, tin oxide, and ITO, with a preferred option being a mixed dielectric layer of zinc oxide doped with Al (AZO) and tin suboxide doped with Al. The refractive index of the bottom capping layer ranges from 1.9 to 2.2, and its thickness ranges from 5 to 30 nm.
[0099] The outer sealing layer is made of gold (Au), a material with excellent chemical stability. Because this product is used in EC dimming films, its principle is based on the electrochemical oxidation-reduction reaction that occurs in the EC material during the power-off process, thereby achieving the dimming function.
[0100] The addition of Au material as a second top capping layer to the second conductive film of this invention further enhances the electrochemical resistance and durability of the product. Au material is absorbent, with an extinction coefficient k-value of approximately 2.3 (550 nm).
[0101] Therefore, adding a second top capping layer will result in some loss of light transmittance, and the thickness of the Au capping layer must be controlled within the range of 2-3.5nm.
[0102] The outer capping layer is made of a high refractive index material, including but not limited to niobium oxide, silicon nitride, titanium oxide, zirconium oxide and other high refractive index oxides or nitrides. The refractive index of the outer capping layer is in the range of 2.0-2.40 and the thickness is in the range of 5-30nm.
[0103] I. Experimental Materials and Equipment
[0104] Substrates: PET (188μm, 100μm), PI (125μm);
[0105] Coating materials: AZO target (zinc oxide: aluminum oxide = 98.5%: 1.5%), tin oxide target, Ag alloy target, Au target, niobium pentoxide target, silicon nitride target, titanium dioxide target;
[0106] Equipment: Micro-gravure roller coating machine, UV curing machine, magnetron sputtering coating machine (background vacuum ≤5×10⁻⁶) -5 Pa), four-probe sheet resistance meter, spectrophotometer (380-780nm), salt spray test chamber (5%NaCl, 37℃), charge and discharge test system (1V / -1V pulse, 1Hz).
[0107] The composition of the hardening layer slurry is as follows:
[0108]
[0109] Example 1
[0110] The EC metal conductive film in this embodiment uses a 188μm thick PET substrate and is coated with a 1μm thick first hardening layer and a second hardening layer on both sides. The main component of the hardening layer is acrylic resin with a refractive index of 1.52.
[0111] On the second hardened layer, a bottom capping layer (AZO), a first silver functional layer, an intermediate dielectric layer (tin oxide), a second silver functional layer, a first top capping layer (AZO), and an outer capping layer (Nb₂O₅) are sequentially deposited using magnetron sputtering, with thicknesses of 23 nm, 6 nm, 30 nm, 9 nm, 25 nm, and 8 nm, respectively. The AZO films are obtained using an AZO target sputtering method, with a composition ratio of zinc oxide:aluminum oxide = 98.5%:1.5 wt%. The first and second silver functional layers are obtained using an Ag alloy target sputtering method, with a composition ratio of Ag:Ni:Cu = 98.5%:1.0%:0.5% wt.
[0112] Example 2
[0113] The EC metal conductive film in this embodiment uses a 188μm thick PET substrate and is coated with a 1μm thick first hardening layer and a second hardening layer on both sides. The main component of the hardening layer is acrylic resin with a refractive index of 1.52.
[0114] On the second hardened layer, a bottom capping layer (AZO), a first silver functional layer, an intermediate dielectric layer (tin oxide), a second silver functional layer, a first top capping layer (AZO), and an outer capping layer (Si3N4) are sequentially deposited using magnetron sputtering, with thicknesses of 23 nm, 6 nm, 30 nm, 9 nm, 25 nm, and 8 nm, respectively. The AZO films are obtained using an AZO target sputtering method, with a composition ratio of zinc oxide:aluminum oxide = 98.5%:1.5 wt%. The first and second silver functional layers are obtained using an Ag alloy target sputtering method, with a composition ratio of Ag:Ni:Cu = 98.5%:1.0%:0.5% wt.
[0115] Example 3
[0116] The EC metal conductive film in this embodiment uses a 188μm thick PET substrate and is coated with a 1μm thick first hardening layer and a second hardening layer on both sides. The main component of the hardening layer is acrylic resin with a refractive index of 1.52.
[0117] On the second hardened layer, a bottom capping layer (AZO), a first silver functional layer, an intermediate dielectric layer (tin oxide), a second silver functional layer, a first top capping layer (AZO), and an outer capping layer (Nb₂O₅) are sequentially deposited using magnetron sputtering, with thicknesses of 23 nm, 7.5 nm, 30 nm, 7.5 nm, 25 nm, and 8 nm, respectively. The AZO films are obtained using an AZO target sputtering method, with a composition ratio of zinc oxide:aluminum oxide = 98.5%:1.5 wt%. The first and second silver functional layers are obtained using an Ag alloy target sputtering method, with a composition ratio of Ag:Ni:Cu = 98.5%:1.0%:0.5% wt.
[0118] Example 4
[0119] The EC metal conductive film in this embodiment uses a 188μm thick PET substrate and is coated with a 1μm thick first hardening layer and a second hardening layer on both sides. The main component of the hardening layer is acrylic resin with a refractive index of 1.52.
[0120] On the second hardened layer, a bottom capping layer (AZO), a first silver functional layer, an intermediate dielectric layer (tin oxide), a second silver functional layer, a first top capping layer (AZO), a second top capping layer (Au), and an outer capping layer (Nb₂O₅) are sequentially deposited using magnetron sputtering, with thicknesses of 23 nm, 6 nm, 30 nm, 9 nm, 25 nm, 3 nm, and 8 nm, respectively. The AZO films are obtained using AZO target sputtering, with a composition ratio of zinc oxide:aluminum oxide = 98.5%:1.5 wt%. The first and second silver functional layers are obtained using Ag alloy target sputtering, with a composition ratio of Ag:Ni:Cu = 98.5%:1.0%:0.5% wt.
[0121] Example 5
[0122] The EC metal conductive film in this embodiment uses a 188μm thick PET substrate and is coated with a 1μm thick first hardening layer and a second hardening layer on both sides. The main component of the hardening layer is acrylic resin with a refractive index of 1.52.
[0123] On the second hardened layer, a bottom capping layer (AZO), a first silver functional layer, an intermediate dielectric layer (tin oxide), a second silver functional layer, a first top capping layer (AZO), a second top capping layer (Au), and an outer capping layer (Si3N4) are sequentially deposited using magnetron sputtering. The thicknesses are 23 nm, 6 nm, 30 nm, 9 nm, 25 nm, 3 nm, and 8 nm, respectively. The AZO films are obtained using AZO target sputtering, with a composition ratio of zinc oxide:aluminum oxide = 98.5%:1.5 wt%. The first and second silver functional layers are obtained using a pure Ag target sputtering.
[0124] Example 6
[0125] The EC metal conductive film in this embodiment uses a 188μm thick PET substrate and is coated with a 1μm thick first hardening layer and a second hardening layer on both sides. The main component of the hardening layer is acrylic resin with a refractive index of 1.52.
[0126] On the second hardened layer, a bottom capping layer (AZO), a first silver functional layer, an intermediate dielectric layer (tin oxide), a second silver functional layer, a first top capping layer (AZO), a second top capping layer (Au), and an outer capping layer (Nb₂O₅) are sequentially deposited using magnetron sputtering, with thicknesses of 23 nm, 7.5 nm, 30 nm, 7.5 nm, 25 nm, and 8 nm, respectively. The AZO films are obtained using AZO target sputtering with a composition ratio of zinc oxide:aluminum oxide = 98.5%:1.5 wt%. The first and second silver functional layers are obtained using Ag alloy target sputtering with a composition ratio of Ag:Ni:Cu = 98.5%:1.0%:0.5% wt.
[0127] Example 7 (for AR glasses: thin substrate + high light transmittance)
[0128] The only difference between the EC metal conductive film in this embodiment and that in Embodiment 1 is: substrate: PET (100μm, to meet the thin and light requirements of AR glasses).
[0129] Thickness of each layer (nm): bottom capping layer (AZO, 20) → first silver functional layer (7) → intermediate dielectric layer (tin oxide, 35) → second silver functional layer (8) → first top capping layer (AZO, 20) → outer capping layer (titanium dioxide, 10);
[0130] Preparation process: The hardening layer adopts slit coating (higher precision), UV curing strength is 1000mJ / cm²; magnetron sputtering power is 120W, speed is 1m / min;
[0131] Example 8 (For automotive side windows: PI substrate + high temperature resistance)
[0132] The only difference between the EC conductive film in this embodiment and that in Embodiment 4 is:
[0133] Substrate: PI (125μm, temperature resistance >200℃, suitable for high-temperature automotive environments);
[0134] Layer thickness (nm): Bottom capping layer (AZO, 25) → First silver functional layer (6.5) → Intermediate dielectric layer (tin oxide, 80) → Second silver functional layer (9.5) → First top capping layer (AZO, 28) → Second top capping layer (Au, 3.2) → Outer capping layer (silicon nitride, 11).
[0135] Ag alloy composition: Ag:Co:Sn=97%:2%:1% (Co improves temperature resistance);
[0136] Performance testing: No abnormalities were observed after 50 cycles of hot and cold cycling from -40℃ to 120℃, indicating that the temperature resistance requirements for automotive side windows are met.
[0137] Example 9 (High corrosion resistance scenario: Ag-Pd alloy + thick Au layer)
[0138] The only difference between the EC conductive film in this embodiment and that in Embodiment 4 is:
[0139] Substrate: PET (188μm);
[0140] Thickness of each layer (nm): bottom capping layer (AZO, 30) → first silver functional layer (7) → intermediate dielectric layer (tin oxide, 90) → second silver functional layer (8) → first top capping layer (AZO, 30) → second top capping layer (Au, 3.5) → outer capping layer (niobium pentoxide, 12).
[0141] Ag alloy composition: Ag:Pd:Cr=98%:1.5%:0.5% (Pd improves corrosion resistance);
[0142] Performance tests show that it is suitable for the high salt spray environment of architectural glass in coastal areas.
[0143] Comparison Sample 1
[0144] Using a 188μm thick PET substrate, a first hardening layer and a second hardening layer with a thickness of 1μm are coated on both sides using a coating method. The main component of the hardening coating is acrylic resin with a refractive index of 1.52.
[0145] On the second hardening layer, a bottom capping layer (AZO), a pure silver functional layer 1, an intermediate dielectric layer (tin oxide), a pure silver functional layer 2, a first top capping layer (AZO), and an outer capping layer (Nb₂O₅) are sequentially deposited using magnetron sputtering, with thicknesses of 23 nm, 6 nm, 30 nm, 9 nm, 25 nm, and 8 nm, respectively. The AZO films are obtained using AZO target sputtering, with a composition ratio of zinc oxide:aluminum oxide = 98.5%:1.5 wt%. The silver functional layer is obtained using a pure Ag target sputtering.
[0146] Comparison Sample 2
[0147] Using a 188μm thick PET substrate, a first hardening layer and a second hardening layer with a thickness of 1μm are coated on both sides using a coating method. The main component of the hardening coating is acrylic resin with a refractive index of 1.52.
[0148] On the second hardening layer, a bottom capping layer (AZO), a silver functional layer, a first top capping layer (AZO), and an outer capping layer (Nb₂O₅) are sequentially deposited using magnetron sputtering, with thicknesses of 30 nm, 15 nm, 30 nm, and 10 nm, respectively. The AZO films are obtained using AZO target sputtering, with a composition ratio of zinc oxide:aluminum oxide = 98.5%:1.5 wt%. The silver functional layer is obtained using a pure Ag target sputtering.
[0149] The above embodiments and comparative examples are summarized as follows:
[0150]
[0151] The above embodiments and comparative examples were subjected to performance tests, including impedance, transmittance, salt spray resistance, and charge / discharge stability.
[0152]
[0153] Surface impedance was measured directly using a four-probe sheet resistance meter.
[0154]
[0155] As can be seen from the table above, the surface impedances of Examples 1-9 and Comparative Examples 1 and 2 are all similar, remaining close to 3Ω / □.
[0156] As can be seen from the table above, Examples 1-3 and 7 are conductive films with a first structure, exhibiting a transmittance of over 86% in the visible light band. Examples 4-6 and 8-9 are conductive films with a second structure, exhibiting a transmittance of over 85% in the visible light band. Comparative Example 1 is similar to the first structure conductive film (Ag alloy was replaced with pure Ag), and its transmittance is close to that of Examples 1-3 and 7. Comparative Example 2 is a single-silver structure, with a significantly lower transmittance.
[0157] Salt spray resistance test: Place the sample in a salt spray test chamber with a salt spray mass fraction of 5% and a test temperature of 37℃. Observe the film surface condition by continuously spraying salt spray.
[0158]
[0159] Charge-discharge stability: Since this product is used in EC (Electronic Color Changing) lighting scenarios, charge-discharge stability is a crucial performance characteristic. The experimental approach is as follows:
[0160] like Figure 2 The entire circuit loop is shown, where the output power supply provides a constant voltage output (voltage setting 0.5-2V). An oscilloscope can be used to observe voltage changes in real time. The conductive solution is a mixture of lithium hexafluorophosphate, methyl carbonate, and ethylene carbonate in a 1:1:1 molar ratio. The conductive films are spaced at a fixed interval, and the oscilloscope voltage and film surface damage are observed in real time after power is applied.
[0161] The voltage setting for this test is a DC pulse, with voltages of 1V and -1V, and a frequency setting of 1Hz. Figure 3 As shown; the conductive ITO films face each other, maintaining a distance of 10 mm. To avoid the generation of trace amounts of hydrogen fluoride (HF) gas during discharge, the entire test setup is placed inside a glove box with good ventilation.
[0162] The results of the charge-discharge stability test are as follows:
[0163]
[0164] As can be seen from the table above, Comparative Example 1 has poor charge-discharge stability, Examples 1-3, 7 and Comparative Example 2 have good charge-discharge stability, and Examples 4-6 and 9 have excellent charge-discharge stability.
[0165] Compared with the prior art, the advantages of the present invention are as follows:
[0166] Significantly improve color-changing speed: By replacing ITO with Ag alloy, the impedance is reduced from over 6Ω / □ to ≤3Ω / □, and the EC color-changing time is shortened from >1min to ≤20s, meeting the rapid response requirements of automobiles and AR glasses;
[0167] Breakthrough in high transmittance: The double silver structure and optical matching design increase the transmittance from ≤81% of existing metal films to ≥83%, and the first structure conductive film can even reach ≥86%, which is better than the transmittance requirements of EC dimming.
[0168] Significantly improved environmental stability:
[0169] Salt spray resistance: The first structure conductive film showed no abnormalities for 168 hours, and the second structure conductive film (including Au layer) showed no abnormalities for 240 hours, far exceeding the existing ITO film (usually ≤100 hours).
[0170] Charge-discharge stability: The first structure conductive film remains undamaged after 500 hours, and the second structure conductive film remains undamaged after 1000 hours, meeting the long-term electrochemical cycling requirements of EC materials;
[0171] Strong adaptability to different scenarios: The two structures are respectively adapted to architectural glass (first structure conductive film, lower cost) and automotive sunroof / AR glasses (second structure conductive film, highly durable), with a wide range of applications.
[0172] All the above embodiments meet the core indicators of "surface impedance ≤ 3Ω / □, light transmittance ≥ 83%", and the salt spray resistance and charge-discharge performance of the second structure conductive film are significantly better than those of the first structure conductive film. The supplementary embodiments further verify the adaptability of the present invention to different substrates (PET / PI) and different scenarios (AR glasses / automobiles / coastal buildings), proving the stability and scalability of the technical solution.
[0173] In summary, the conductive metal film for EC (electrode switching) of this invention, through its double silver functional layer, optical matching, and special sealing layer design, solves the pain points of existing EC dimming films, namely "slow color change, low light transmittance, and poor corrosion resistance." It can be mass-produced (using mature coating + magnetron sputtering processes) and its cost is comparable to existing ITO films (using less Ag alloy, with a total double silver layer thickness of only 14-18 nm). Its two structures are suitable for applications such as architectural glass, automotive sunroofs, and AR glasses, demonstrating significant industrial application value.
[0174] It will be apparent to those skilled in the art that this disclosure is not limited to the details of the exemplary embodiments described above, and that this disclosure can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of this disclosure is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within this disclosure. No reference numerals in the claims should be construed as limiting the scope of the claims.
[0175] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A metal conductive film for EC, comprising a first hardening layer, a flexible substrate, a second hardening layer, a bottom capping layer, a first silver functional layer, an intermediate dielectric layer, a second silver functional layer, a first top capping layer, and an outer capping layer disposed sequentially. The total thickness of the first silver functional layer and the second silver functional layer is 14-18 nm, and d2-d1≤4 nm, where d1 is the thickness of the first silver functional layer and d2 is the thickness of the second silver functional layer.
2. The metal conductive film for EC according to claim 1, characterized in that, The first silver functional layer and / or the second silver functional layer are silver layers or silver functional layers, wherein the silver functional layer is a doped metal with a doping atomic ratio of 0.5%-5% in silver, and the doped metal is one or more of Ni, Cu, Co, Sn, Pd, and Cr.
3. The metal conductive film for EC according to claim 1, characterized in that, The outer capping layer is a high refractive index material with a refractive index of 2.0-2.40, selected from one of Nb2O5, Si3N4, TiO2, and ZrO2; its thickness is 5-30 nm.
4. The metal conductive film for EC according to claim 1, characterized in that, The bottom capping layer and / or intermediate medium layer and / or the first top capping layer are made of oxides of In, Sn, Zn, and Cd or their composite multi-element oxides.
5. The metal conductive film for EC according to claim 1, characterized in that, The thickness of the flexible substrate is 0.05-3mm, and its raw materials are selected from one or more of PET, PI, SRF, TAC, COP, PMMA, PE, PC, PP, PA, and TPU.
6. The metal conductive film for EC according to claim 1, characterized in that, The first hardening layer and / or the second hardening layer have a refractive index of 1.46-1.56 and a thickness of 0.1-5 μm, and the layer includes low refractive index particles, which are silicon oxide, aluminum oxide or MgF2.
7. The metal conductive film for EC according to any one of claims 1-6, characterized in that, It also includes a second top capping layer formed between the first top capping layer and the outer capping layer, which is an Au layer with a thickness of 2-3.5 nm.
8. The method for preparing a conductive metal film for EC according to any one of claims 1-7, comprising the following steps: (1) Substrate pretreatment: Clean and dry the flexible substrate to remove surface oil and impurities; (2) Hardening layer preparation: A first hardening layer and a second hardening layer are formed on both sides of the substrate by coating; (3) Vacuum coating: A bottom capping layer, a first silver functional layer, an intermediate dielectric layer, a second silver functional layer, and a first top capping layer are sequentially prepared on the second hardened layer by magnetron sputtering. The first top capping layer may also selectively form any of the following: a. External capping layer; b. Second top capping layer, external capping layer.
9. A dimming assembly, comprising a light-transmitting body and a metal conductive film for EC formed on the light-transmitting body according to any one of claims 1-7.
10. The application of the dimming component according to claim 9 in a device having a window structure, wherein the window structure includes a frame and a dimming component disposed on the frame.
